GENDER JUSTICE IN THE SHARING OF INHERITANCE AND IMPLEMENTATION IN INDONESIA - Hisam Ahyani; Haris Maiza Putra; Muharir Muharir; Encep Taufik Rahman; Mustofa Mustofa (Asy-Syari'ah, 2022)
Abstract: Fairness in inheritance distribution between men and women in Indonesia is still an exciting topic to discuss. It is proven that classical Islamic thought says that men’s and women’s portions in inheritance distribution are final, as stated in the Qur'an Surat an-Nisa verse 11. However, contemporary Islamic thought sees it as a rule that needs to be contextualized to current situations. This progressive thinking about inheritance distribution was pioneered by gender activists who saw that Fiqh Mawaris has a gender bias and discrimination. Therefore, the application of the "gender-friendly justice" concept in the inheritance distribution in Indonesia needs to be put forward. This research analyses the "gender-friendly justice" concept in inheritance law and its application in Indonesia. This study uses Sigmund Freud's gender theory, with an analytic descriptive method focusing on the problem of inheritance distribution in Indonesia. The research results prove that the concept of "gender-friendly justice" in the inheritance distribution refers to the agreement principle and the gender equity principle, where the application is carried out based on the fairness principle. The gender equality principle is implemented by prioritizing the concept of rahmatan lil'alamin, namely equality as servants and caliph of Allah, equality in receiving primordial agreements and cosmic drama events, and reaching achievements.Abstrak: Keadilan pembagian harta waris di Indonesia antara laki-laki dan perempuan masih menjadi bahan diskusi yang menarik. Pemikiran Islam klasik menyatakan bahwa pembagian harta warisan bagi laki-laki dan perempuan sudah dianggap final, sebagaimana disinggung dalam Al-Qur’an surah an-Nisa ayat 11. Namun, pemikiran Islam kontemporer melihat hal tersebut sebagai aturan yang perlu dikontekstualisasikan sesuai perkembangan zaman. Pemikiran progresif tentang pembagian waris ini dipelopori oleh para pegiat gender yang melihat fiqih mawaris masih bersifat bias gender yang dapat menimbulkan diskriminasi gender, sehingga penerapan konsep “keadilan ramah gender” dalam pembagian harta waris di Indonesia perlu dikedepankan. Tujuan penelitian ini adalah untuk menganalisis konsep “keadilan ramah gender” dalam hukum waris dan penerapannya di Indonesia. Penelitian ini menggunakan teori gender Sigmund Freud, dengan metode deskriptif analitik yang memusatkan perhatian pada masalah pembagian waris di Indonesia. Hasil riset membuktikan bahwa konsep “keadilan ramah gender” dalam pembagian harta waris mengacu pada prinsip kesepakatan dan prinsip keadilan gender bagi anak laki-laki dan perempuan, dimana penerapannya dilakukan berdasarkan atas asas keadilan. Penerapan prinsip kesetaraan gender ini diterapkan dengan mengedepankan konsep rahmatan lil’alamin yakni penyetaraan sebagai hamba dan khalifah Allah, penyetaraan menerima perjanjian primordial, penyetaraan dalam peristiwa drama kosmis, dan penyetaraan dalam meraih prestasi.